Model Manajemen Strategik Pengembangan Kinerja untuk Meningkatkan Produktivitas Dosen pada Perguruan Tinggi Swasta - Wati Irnawati (Journal of Education and Teaching (JET), 2023)
The purpose of the study is to create a strategic management model for improving institutional performance at private tertiary institutions by increasing lecturer productivity. Researchers use the Four D Model research design with four stages and the Research and Development (R&D) strategy (Define, Design, Develop and Disseminate). The study was carried out at Universitas Putra Indonesia (UNPI) Cianjur, with the chancellor, head of the LPPM, dean, head of study program, and lecturer serving as informants. The collecting of data was done by observation, interviews, document studies, and focus group discussions (FGDs) in order to test the data, determine its meaning, and place the data in the appropriate theoretical frameworks. The study's findings indicate that strategic management for lecturer performance development has been successfully implemented because the average percentage of strategic management indicators for performance development achievement is 75.70%. With an achievement percentage of 80.55%, the strategic planning component had the highest success rate. The follow-up component, however, had the lowest success rate (67.73%). To boost lecturer productivity at private tertiary institutions, a performance development strategy management model that consists of a number of interconnected model components was designed.